Pengaruh Penambahan Arang Tempurung Kelapa Terhadap Durabilitas Campuran Asphalt Concrete Wearing Course (AC-WC) - Putri, Alfina Dwi; Putra, Sasana; Sulistyorini, Rahayu; Herianto, Dwi (Universitas Lampung, 2022)
With the rise in the number of vehicles on Indonesian roads, the frequency of loads that occur on road pavements rises, and extreme weather changes can damage the pavement layer, particularly at the level of durability (durability), particularly at the top layer, namely the AC-WC (Asphalt Concrete Wearing Course). As a result, it is required to improve the quality of road surface, one of which is to add additives to asphalt mixtures. Coconut shell waste, which is converted into charcoal, was used as an additive in this study. Because coconut shell waste is readily available in Indonesia, but its utilization is inefficient, this study intends to assess the effect of adding coconut shell charcoal at levels of 0%, 3%, 6%, and 9% on the durability of asphalt mixtures. Furthermore, the test objects at each level of coconut shell charcoal were submerged for 30 minutes, 1 day, 7 days, and 14 days at a temperature of 60˚C. Because coconut shell charcoal is an organic material, it is susceptible to the influence of water, the effect of adding coconut shell charcoal to the AC-WC mixture in terms of the First Durability Index (IDP) and Second Durability Index (IDK) values show a greater loss of strength as the coconut shell charcoal content increases.